Implementasi Marketing Automation Menggunakan Metode Search Engine Optimization (SEO) On Page dan Off Page pada Website Berbasis Content Management System (CMS) pada PT. Eltama Prima Indo - Reyhan Ivandi; Yusi Tyroni Mursityo; Widhy Hayuhardhika Nugraha Putra (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2021)
PT Eltama Prima Indo is a company engaged in the chemicals sector which provides services in the form of epoxy paint products, epoxy coating, and sandblasting services. Along with the rapid development of technology, PT Eltama Prima Indo wants to maximize technology as their marketing medium, especially Google search engine. However, PT Eltama Prima Indo does not yet have a page or website that is intended for search engine optimization. Therefore, this study begins with the development of a website with the address https://www.epoxynesia.com using the Wordpress Content Management System (CMS). Then proceed with website optimization on the Google search engine using the on page and off page Search Engine Optimization (SEO) method. This study uses research & development or implementative methods to test the effectiveness of on-page and off-page SEO implementation on keyword rankings, performance, and the number of epoxynesia.com visitors on Google search engine. Based on the analysis of SEO and competitors, epoxynesia.com is known to require the implementation of on page SEO and off page SEO to adjust the website to the rules of the Google algorithm to compete with competitors. After the analysis is carried out, the authors continue to implement on-page and off-page SEO. Then, the implementation results are tested using several tools to determine the changes in the ranking of keywords, performance, and visitors that are obtained. Based on the results of these tests, there was an increase in keyword rankings, performance, and visitors. In addition, the increase in the SEO authority score for the domain authority version of Moz increased by 14 points. Meanwhile, the Ahrefs version of the domain rating increased by 31 points.